Pengembangan Prototipe Dan Pengujian Traktor Satu Roda Untuk Pemeliharaan Tanaman Padi - Jusran Jusran; Radite Praeko Agus Setiawan; I Dewa Made Subrata (Jurnal Keteknikan Pertanian, 2019)
Most of paddy fields in Indonesia are not consolidated, therefore, soil hardpan usually did not exist.  With no soil hardpan, mobility of any machine for crop maintenance is very difficult even in some places is almost impossible.Until now crop maintenance such as weeding, spraying and spreading fertilizer was done manually by labor. Then mechanization is required to replace the labour which is not available or very expensive. Hence, this study conducted with objective to make a prototype II of a single wheel tractor  for crop maintenance operated in deep mud field or in an unconsolidated paddy field. The study also did performance test of a single wheel tractor to measure the tractor speed, traction, sinkage, and slip of wheel  when operated in rice plants field. The results of performance test showed that the speed average of wheel with straight lug and curved lug were 1.15km/hour and 0.97 km/hour. The average of sinkage and slip both of wheels with straight lug and curved lug respectively were 24.8 cm, 25.9 cm and 38.7 %, 26.12%. The results of performance test olso showed that the traction average of wheel with straight lug and curved lug respectively were 45.8 kg and 41.5 kg